2007
DOI: 10.1029/2007ja012327
|View full text |Cite
|
Sign up to set email alerts
|

A method for determining the drift velocity of plasma depletions in the equatorial ionosphere using far‐ultraviolet spacecraft observations

Abstract: [1] The Far-Ultraviolet Imager (IMAGE-FUV) on board the NASA IMAGE satellite has been used to observe plasma depletions in the nightside equatorial ionosphere. Observations from periods around spacecraft apogee, during which equatorial regions are visible for several hours, have allowed the velocity of these plasma depletions to be determined. A new method for determining the velocity of these depletions using an image analysis technique, Tracking Of Airglow Depletions (TOAD), has been developed. TOAD allows t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 20 publications
2
28
0
Order By: Relevance
“…However, our simplified 3-D bubble reconstruction method is not capable of producing the altitude and latitude plasma distribution in a plasma depletion shell. We have chosen the arch-shaped emission depletion to demonstrate the formation of a plasma depletion shell but there exist different optical bubble morphologies that are variable with local time and longitude [e.g., Kil et al, 2006;Park et al, 2007]. The optical bubble image is a trace of the 3-D bubble structure at the F peak height and therefore the shell structure varies depending on the optical bubble morphology.…”
Section: Discussionmentioning
confidence: 99%
“…However, our simplified 3-D bubble reconstruction method is not capable of producing the altitude and latitude plasma distribution in a plasma depletion shell. We have chosen the arch-shaped emission depletion to demonstrate the formation of a plasma depletion shell but there exist different optical bubble morphologies that are variable with local time and longitude [e.g., Kil et al, 2006;Park et al, 2007]. The optical bubble image is a trace of the 3-D bubble structure at the F peak height and therefore the shell structure varies depending on the optical bubble morphology.…”
Section: Discussionmentioning
confidence: 99%
“…The eastward drift velocity of the F region plasma has a maximum value at ∼20:00 LT, then gradually decreases, and becomes nearly zero near dawn. The zonal drift velocity of plasma bubbles and its variation with local time are similar to those of the average F region plasma drift [ Valladares et al , 1996; Immel et al , 2003; Park et al , 2007]. If a series of plasma bubbles exists and drifts eastward with the pattern of the average F ‐region plasma drift, the drift velocity of a bubble in the western (trailing) side is always faster than that of the bubble in the eastern (leading) side.…”
Section: Observationsmentioning
confidence: 99%
“…The Jicamarca radar measurements show that the average zonal drift of the equatorial ionospheric F region plasma is eastward at night and becomes westward near dawn [ Fejer et al , 1991, 2005]. The zonal drift velocity of the plasma depletions and its variation with local time are similar to those of the average F region plasma drift [ Abdu et al , 1985, 2003; Valladares et al , 1996; Taylor et al , 1997; Sobral et al , 1999; Immel et al , 2003, 2004; Park et al , 2007]. It was suggested that the depletions are embedded in the surrounding plasma and that the zonal drift velocity of the depletions can be used as an indicator of the ambient plasma drift.…”
Section: Introductionmentioning
confidence: 99%